Kelas Sosial VS Pendapatan: Eksplorasi Faktor Penentu Pembelian Consumer Goods Dan Jasa - Anna Triwijayati; Deviga Bayu Pradipta (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2018)
Social class and income influence consumer purchase behaviour. This study aims to determine the relationship and difference between social class and income by purchasing consumer goods and services in Malang. This research used a quantitative survey ex-post-facto method. Research respondents were classified based on their level of income and social class using the Index of Social Position (ISP). The questionnaire contains 18 items of purchase, grouped into 5 types namely: food and drink, clothing, durable goods, investment, services and other products. The data analysis technique used chi-square. The results of the analysis show that social class is associated with the purchase of 17 items, while income is associated with all items of goods and services consumed. Social class is more associated with fast food, clothes, electronic equipment, price and amount of investment and finance; income is more associated with meat, milk, the type of vehicle used, ownership of electronic tools, type of investment and finance, and housing and other buildings.